What are the characteristics of patients with a stroke who are believed to need a pre-discharge home visit by occupational therapists? - Whitehead, Phillip J. (2013)
Pre-discharge home visits are commonly completed by occupational therapists as part of the stroke rehabilitation care pathway. However, wide variations have been reported between stroke units in the number of home visits completed (Drummond et al 2012a; Royal College of Physicians 2006). This research aimed to identify the characteristics of those patients who are believed to need a visit by occupational therapists. Such a study is important as there is currently limited guidance to indicate when a home visit should be completed, or which particular patients should have a home visit. This has implications in terms of standardising practices between occupational therapists and provision of equitable services to patients.